Worldmaking Toward the Symbiocene Era: Transition Design in Community Sustainability and Climate Education - Lange, Elizabeth A.; Houlden, Shandell (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2026)
With the pressing realities of climate change, biodiversity loss, and eco‑anxiety, we reconceive community adult education in the service of sustainable and regenerative futures. We assert that the environmental crisis is, in part, a design crisis, and therefore, using transition design and relationality theory, we approach pedagogy as designing for the transition to the Symbiocene era. In our Canadian comparative case study involving a large urban city and a semi‑rural community, we derived three pedagogy pathways from the first case, which have been adapted and studied in the second case. These pathways were the power of story, connecting individual and community needs, and fostering kinship with the natural world. The interpenetration of these pathways encouraged adult engagement, overcame resistance, and created openness to civic involvement. In this article, we first describe in detail how we developed the pedagogy in relation to the context of each case. We then offer a preliminary analysis of how designing for the identified pathways manifests transition design. We consider such learning to be worldmaking, in that interactive design unleashes self‑organizing energies, fosters an ontological perceptual shift toward communal individuality, and alchemically transforms local stories as constitutive of a new world where we are designing ourselves back into the dance of life.